2019
DOI: 10.1371/journal.pone.0211771
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to gestational diabetes mellitus increases developmental defects in the enamel of offspring

Abstract: Background and objective Gestational diabetes mellitus (GDM) is associated with short- and long-term maternal and perinatal repercussions. Our objective was to evaluate the long-term consequences of intrauterine exposure to hyperglycemia on Developmental Defects of Enamel (DDE) in offspring. Results Overall, 50 children of women with GDM and 250 children of normoglycemic women participated, the latter serving as controls. Children were examined at the age between 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
9
0
2
Order By: Relevance
“…26 Epidemiological and animal model studies have shown that hyperglycemia alters the tooth enamel development process and affects tooth eruption and mineralization. 27 Pascon et al observed that gestational diabetes was associated with the presence of enamel defects in the children of mothers with the condition, with higher prevalence of demarcated opacities, corroborating the data found in the present study. 27 In a study by Prakash et al, 28 respiratory disorder was the most common complication.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…26 Epidemiological and animal model studies have shown that hyperglycemia alters the tooth enamel development process and affects tooth eruption and mineralization. 27 Pascon et al observed that gestational diabetes was associated with the presence of enamel defects in the children of mothers with the condition, with higher prevalence of demarcated opacities, corroborating the data found in the present study. 27 In a study by Prakash et al, 28 respiratory disorder was the most common complication.…”
Section: Discussionsupporting
confidence: 93%
“…27 Pascon et al observed that gestational diabetes was associated with the presence of enamel defects in the children of mothers with the condition, with higher prevalence of demarcated opacities, corroborating the data found in the present study. 27 In a study by Prakash et al, 28 respiratory disorder was the most common complication. Decreased levels of phosphorus and serum calcium during pregnancy associated with other complications at this time may also result in poor mineralization of tooth enamel.…”
Section: Discussionsupporting
confidence: 93%
“…There are reports of the occurrence of tooth eruption delay and changes in the eruption sequence 6,8 lip hypotonia, absence of lip sealing and mouth breathing 3 and enamel opacity. 5,8 Carvalho et al, 11 described that, in a population of 30 children with this condition, 20% had inadequate tongue position at rest and also registered the presence of short labial or lingual curb, micrognathia, changes in the shape or number of teeth and spasms muscle.In addition to bone development, systemic, local or hereditary disorders that occur during enamel development can cause anomalies in its structure, affecting deciduous and / or permanent dentition [12][13][14] and these dental enamel development defects (DDE) predispose to a greater risk of dental caries. 15,16 According toLunardelli& Peres 17 the extent of the defect will depend on factors such as intensity and duration of the etiologic agent and period of crown formation.…”
Section: Introductionmentioning
confidence: 99%
“…19 Maternal disorders such as malnutrition and lack of vitamin A, which is responsible for the immune function and growth of ameloblastic cells, calcium and phosphorus deficiency, as well as other systemic events (diabetes, hypertension, congenital syphilis, exanthematic diseases), traumatic, environmental or genetic, can alter the cellular architecture and metabolism during the deposition of the organic matrix causing defects in the enamel structure. [12][13][14] In addition, other events have also been associated with DDE in recent investigations: the use of laryngoscope and endotracheal intubation, prolonged mechanical ventilation and oral tube nutrition, mandibular fractures, surgical trauma, and repair of cleft lip and palate 19 in addition to prematurity and low weight. 20,21 Thus, the objective of this study was to describe oral problems and oral health habits in children in early childhood with microcephaly associated with fetal exposure to the ZIKV and to verify factors potentially associated with the occurrence of DDE in this population.…”
Section: Introductionmentioning
confidence: 99%
“…У зв'язку з широким поширенням хвороб тканин пародонта і твердих тканин зубів особлива увага вчених привертається до питань формування цих тканин. Віддалені наслідки перинатальної патології, зокрема вплив вагітності, яка патологічно протікає, на формування стоматологічних порушень на сьогоднішній день є парадигмою [1,2,3].…”
unclassified